PERBEDAAN PERILAKU PENCEGAHAN DBD DAN KEPADATAN VEKTOR PADA KELOMPOK POST DAN TANPA INTERVENSI KOMUNIKASI PERUBAHAN PERILAKU (KPP) - Lestari, Nita Dwi; Martini, Martini; Saraswati, Lintang Dian; Hestiningsih, Retno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Communication for Behavioral Impact (KPP / COMBI) is a communication method to optimize mosquito nest eradication (PSN-DBD), which is implemented in accordance with the characteristics of target communities, and emphasizes teamwork (across health and cross-sectoral programs). Through KPP / COMBI the public gets information about DHF and prevention, recognizing problems in the region and determining the solutions with the resources they have. The optimization of PSN-DBD is expected to have an impact on dengue vector control in the community. The purpose of this study is to distinguish the prevention behavior of dengue fever and vector density in the post area and without the intervention of KPP / COMBI in Gunungkidul Regency. This type of research is observational analytic research with comparative study design of cross sectional approach. The instrument used was questionnaire and larva observation sheet. The sample of research is 80 with Probability Proportional to Size technique. The results showed that there was a significant difference in knowledge (p = 0,045) attitude (p = 0.0001), and practice (p = 0.0001) between post intervention area and without KPP / COMBI intervention. Vector surveys in the post intervention area showed 75% ABJ, 25% HI, 12% CI, and BI 35 better than those without KPP / COMBI intervention, ABJ 55%, HI 45%, CI 26%, and BI 67.5 . Knowledge, attitudes and practice of preventing DHF is better in the post-intervention area of KPP / COMBI than areas without KPP / COMBI intervention. Suggestion for officers to optimize the application of COMBI method in prevention of DHF and improve monitoring evaluation for PSN-DBD activities.